The stock–bond correlation and macroeconomic conditions: One and a half centuries of evidence - Yang, Jian; Zhou, Yinggang; Wang, Zijun (Journal of Banking & Finance, 2009)
Using monthly stock and bond return data in the past 150 years (1855–2001) for both the US and the UK, this study documents time-varying stock–bond correlation over macroeconomic conditions (the business cycle, the inflation environment and monetary policy stance). There are different patterns of time variation in stock–bond correlations over the business cycle between US and UK, which implies that bonds may be a better hedge against stock market risk and offer more diversification benefits to stock investors in the US than in the UK. Further, there is a general pattern across both the US and the UK during the post-1923 subperiod and during the whole sample period: higher stock–bond correlations tend to follow higher short rates and (to a lesser extent) higher inflation rates.